Studies of clinical symptoms of panleukopenia in cats in the Donetsk People’s Republic - I. V. Berdyukova; P. A. Rudenko (Ветеринария сегодня)
Feline panleukopenia is a highly contagious viral disease of the members of the family Felidae caused by a DNA-virus of the family Parvoviridae. After infection, the virus is detected in saliva, nasal discharge, urine and feces; it is transmitted through excrements, water, food, and, according to some reports, by bloodsucking insects. The disease is characterized by gastrointestinal tract, central nervous system, hematopoietic tissue lesions. The paper describes the clinical signs of panleukopenia in cats in the territory of the Donetsk People’s Republic. Based on the records of a state-financed veterinary hospital and a charitable animal shelter located in the town of Yasinovataya, as well as those of private veterinary clinics and a veterinary office located in Donetsk, a classification of the clinical signs of the disease in pet and stray cats is suggested with the signs grouped according to their occurrence rate and by age groups. The paper provides evidence of feline panleukopenia occurrence in the territory of the Donetsk People’s Republic. In particular, the period from 2015 to 2018 was characterized by an increase in panleukopenia morbidity in stray animals; pet cats were also involved in the epidemic process. It was found that most of the clinical symptoms of panleukopenia were reported in cats of all age categories irrespective of their sex. Specific symptoms characteristic for different age groups were reported. It was found that panleukopenia morbidity rates for stray kittens aged 0–12 months were 1.8 times higher than those for pet kittens of the same age group. The disease was reported in adult pet cats 2.4 times less frequently than in stray cats. It is shown that the number of the disease cases in female cats is 1.5 times higher than in male ones. It is concluded that the violation of quarantine rules and insufficient vaccination coverage in cats are risk factors for the disease outbreak occurrence precipitating the multiple recurrent outbreaks of the disease.